THE PLACE AND ROLE OF KEY COMPETENCE "ENTREPRENEURSHIP AND FINANCIAL LITERACY" IN THE CONTENT OF TECHNOLOGIES OF BASIC SECONDARY EDUCATION - Василевська, Тетяна; Бербец, Віталій (SWorldJournal, 2022)
The article considers the essence of the key competence "Entrepreneurship and initiative" in the process of technological training of primary school students during technology lessons, describes the methodological basis for its implementation in the educ